Analisis Pencapaian Program Tuberkulosis Paru Pada Kelompok Usia Dewasa Dan Lansia Di Wilayah Kerja Puskesmas Bagansiapiapi Kabupaten Rokan Hilir - Dwi Septi Andria; Hetty Ismainar; Romy Cahyadi (Science and Education Journal (SICEDU), 2026)
Pulmonary tuberculosis (TB) remains a major public health problem in Indonesia, including in the working area of Bagansiapiapi Community Health Center (Puskesmas), Rokan Hilir Regency. In 2025, the Treatment Success Rate (TSR) reached 78.3%, which was still below the national target of 90%, particularly among adults and older adults. This study aimed to analyze the achievement of the pulmonary TB program, identify existing problems, determine priority issues, analyze their root causes, and develop intervention strategies to improve program performance. This study employed a qualitative approach using a case study design. Data were collected through field observations, in-depth interviews, and document reviews of the TB program. Data analysis was conducted using the Problem Solving Cycle, with priority problems determined through the Urgency, Seriousness, and Growth (USG) method and root cause analysis performed using the Fishbone Diagram. The findings revealed that the primary problem was the low Treatment Success Rate of pulmonary TB. Contributing factors included the high workload of health workers, suboptimal performance of Treatment Supporters (PMOs), inadequate patient monitoring and education, limited educational media and supporting facilities, information system constraints, insufficient funding, social stigma, and geographical barriers in coastal areas. The proposed interventions include strengthening the capacity of health workers and PMOs, improving patient adherence monitoring, optimizing health education, enhancing patient tracing, and reinforcing cross-sector collaboration. These interventions are expected to improve treatment success rates and support Indonesia's national tuberculosis elimination target.